(untitled) (SAARC Journal of Agriculture, 2016)
A study was undertaken to determine the generation-wise parasitizing efficiency of mass reared Bracon hebetor on wax moth (Galleria mellonella). Two experiments were conducted to achieve the objectives. In the first experiment, the host larvae and parasitoid were released in the field micro plot during first generation and reared in the laboratory in subsequent generations. In another experiment, all generations were developed in the laboratory. In the first experiment, generation showed significant variation on sex ratio of adult progeny production. The male sex ratio increased with the range of 62.89 to 74.58% and female sex ratio declined ranging from 39 to 25% with the advancement of generations. The percent parasitization and adult progeny production was not influenced appreciably with the progress of generation. In the second experiment parasitization and adult progeny production did not vary significantly in successive generations. However there was a decreasing trend in parasitization from 95 to 55% by Bracon hebetor and adult progeny production by 47.5 to 15.5 adultsfemale-110 larvae-1 over generation. The sex ratio of adult progeny was significantly influenced by inbreed generation in laboratory reared population. Female decrease in sex ratio from first to sixth generation was 39.25 to 16.88%. SAARC J. Agri., 13(2): 1-12 (2015)